Patterns in the Adoption of Russian National Traditions by Alaskan Natives - Savelev, Ivan V. (International Journal of Psychosocial Rehabilitation, 2020)
During the past two and a half centuries, the traditions and culture of the native people of Alaska has been affected first by Russian, then by Anglo-American culture. The traces of Russian influence can be observed even now, 150 years after cession of this territory to the US, as verified by the expeditions of Russian America Heritage Project documenting sustained Russian influence, religious in the first place. At the initial stage of exploration of Russian America, influence was predominantly exercised though taking of amanats (hostages) resulting in close contacts between the Russian fur hunters and the representatives of native population. In contrast to Siberia, where this practice originated, Alaskan amanats were treated quite kindly and passed the Russian customs and traditions to their kin. After Russian American Company was established, Orthodox Christianity and the Russian Orthodox Church took over as the primary bearer of the Russian cultural traditions with the men of faith acting as advocates of the native population in the colonial administration among other things. The Russian Orthodox Church retained its authority and influence, as well as its role of the mediator between the civilization, even after cession of Alaska.